Leadership in Catholic Social Teaching - Marek, Agnieszka (Annales. Etyka w Życiu Gospodarczym, 2015)
The material subject of Catholic social science is man and his actions taken in thefields of politics, the economy and society. According to its rules each person shouldbe engaged in building the world through the realization of his or her vocation. Onekind of vocation might be leading people by acting in accordance with the Gospeland teachings of the Church. The most important values for the leader in this casewould be: respect for human dignity and human rights, freedom, justice, the subsidiarity principle and cooperation due to creating the common good. The listed rulesare realized by servant leadership, the idea functioning in the field of managementthat derives its origins from Christ’s speech: whosoever will be chief among you,let him be your servant (Mt 20:27).